Cheias e escassez de água no Alto Alentejo. O exemplo da Bacia Vertente da Ribeira de Tera - Ramos, Catarina (Finisterra, 1995)
FLOODS AND DRYNESS IN ALENTEJO. THE CASE OF THE DRAINAGE BASIN OF RIBEIRA DE TERA (PORTUGAL) - The drainage basin of Ribeira de Tera belongs to the Hydrographic Basin of the River Tagus, and it is located in one of the driest areas of Portugal: Alentejo.The geological formations of the drainage basin have a very reduced permeability, resulting in drastically worsening of the consequences of low and irregular rainfall. The drainage basin is much affected by the dryness, since the rainfall is absent during more than 3/4 of the days of the year and, for more than half of the years (58%), the precipitation does not even reach 700 mm/year. Every stream of the drainage basin is therefore temporary, including its main channel, which stays dry an average of 133 days/year.The early 70's mark a change in the stream's behaviour. The fluvial discharges have been decreasing, and the drought continues throughout the Autumn. The number of flood days is decreasing distinctly, but the flood's magnitude has increased, due to the decrease of floods with low peak flows. These changes in the fluvial regime are directly connected with the precipitation decrease trend and with the construction of dozens of small-sized dams in an attempt to retain the water for irrigation and for the cattle. These small-sized dams are empty by the end of the Summer and they retain the water from the small Autumn floods.The carbonated metamorphic formations occupy 4% of the area of the drainage basin. They constitute its aquifer reservoir. These rocks, together with the volcanic metamorphic ones, supply 65% of the springs of the drainage basin. This aquifer is exposed to great anthropic pressure, not only because it supplies several human activities which develop around the most important population nucleus of the drainage basin (City of Estremoz), but also because it supports one of the rare industries in the region: the marble extraction.From the environemental point of view, the activity of the quarries has a rather negative impact, because it is destroying the only aquifer reservoir in a region very poor in water resources (either superficial or underground); from the economical and social points of view, the decrease in quarry activity is almost unthinkable due to the value of the marble exported as of ornamental rocks and, mainly, because it is one of the rare industries in a region facing severe unemployment prloblems.